Integration of Lossless Data Compression Algorithms with Optical Fiber Transmission: Simulation and Performance Evaluation (Comprehensive Journal of Science, 2025)
The rapid growth of digital data has created a strong demand for efficient compression andreliable high-speed transmission systems. This research presents the design and simulationof an integrated framework that combines lossless data compression with optical fibercommunication. Two widely used algorithms, Huffman coding and LZW, were implementedfor text compression, achieving an average compression ratio of 1:47, while audiocompression employed a down-sampling technique with Fast Fourier Transform (FFT),resulting in an average compression ratio of 1:10 with acceptable signal quality. The opticalfiber system was modeled using OptiSystem software, yielding promising results with a Qfactor of 8.46 dB, Bit Error Rate (BER) of 1.28 × 10⁻¹⁷, and Optical Signal-to-Noise Ratio(OSNR) above 20 dB. These findings confirm the feasibility of integrating compressionalgorithms with optical transmission technologies to enhance storage efficiency and longdistance data transfer. The contributions of this work include: (1) comparative evaluation ofHuffman and LZW performance in terms of compression ratio, speed, and memory usage,(2) analysis of audio compression trade-offs using FFT-based down-sampling, and (3)validation of the integrated system through fiber-optic simulation. This study provides afoundation for future hybrid compression frameworks and AI-driven optimizations to supportnext-generation multimedia communication systems.
Keywords: Data compression, Huffman coding, LZW, FFT, Optical fiber, OptiSystem, Multimedia communication.